2021
DOI: 10.3390/cancers13246265
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Oral Yeast-Derived β-Glucan to Enhance Anti-GD2 Immunotherapy of Resistant High-Risk Neuroblastoma

Abstract: Beta glucans, complex polysaccharides, prime leukocyte dectin-1 and CR3-receptors and enhance anti-tumor cytotoxicity of complement-activating monoclonal antibodies. We conducted a phase I study (clinicaltrials.gov NCT00492167) to determine the safety of the combination of yeast-derived beta glucan (BG) and anti-GD2 murine monoclonal antibody 3F8 in patients with relapsed or refractory high-risk neuroblastoma. Patients received intravenous 3F8 (fixed dose of 10 mg/m2/day × 10 days) and oral BG (dose-escalated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Also, clinical trials can determine the safety of new drugs. To determine the safety of Fermentum-derived β-polysaccharide for the treatment of patients with relapsed or refractory high-risk neuroblastoma, Cardenas et al made Fermentum β-polysaccharide into an oral drug, and 44 patients had varying degrees of relief from tumour symptoms after 141 cycles of the drug ( Cardenas et al, 2021 ). This is certainly good news for the widespread use of Fermentum β-polysaccharide-related drugs in the future.…”
Section: Activitymentioning
confidence: 99%
“…Also, clinical trials can determine the safety of new drugs. To determine the safety of Fermentum-derived β-polysaccharide for the treatment of patients with relapsed or refractory high-risk neuroblastoma, Cardenas et al made Fermentum β-polysaccharide into an oral drug, and 44 patients had varying degrees of relief from tumour symptoms after 141 cycles of the drug ( Cardenas et al, 2021 ). This is certainly good news for the widespread use of Fermentum β-polysaccharide-related drugs in the future.…”
Section: Activitymentioning
confidence: 99%
“…However, the immunomodulatory properties of the targeted CLR must be considered to secure the induction of an inflammatory antitumor immune response. Sometimes, the immune regulatory properties of CLRs can be overridden when they are targeted in combi-nation with adjuvants such as TLR ligands [229,230] or TACA-specific antibodies [231,232]. In some cases, the induction of tolerance can be reverted with coinjection of anti-CD40 antibodies to activate DCs and to inhibit tumour growth [233,234].…”
Section: Taca and Clr Targeting For Cancer Immunotherapymentioning
confidence: 99%
“…The safety and adjuvant effect when given orally was demonstrated in a phase 1 trial . After oral administration to patients, β-glucan was measurable in the blood . Previous preclinical studies found β-glucan localizing in macrophages and transported to the spleen, the lymph nodes, and the bone marrow .…”
Section: Introductionmentioning
confidence: 99%
“…We tested a special gel formulation of yeast-erived β-glucan in mice and were able to show a strong adjuvant effect in enhancing antiganglioside antibody response . The safety and adjuvant effect when given orally was demonstrated in a phase 1 trial . After oral administration to patients, β-glucan was measurable in the blood .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation